STATEHOOD IN THE ERA OF THE NEW WORLD ORDER (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The article «Statehood in the Era of the New World Order» is devoted to the analysis of the transformation of the institution of the state through the prism of the crisis and rethinking of state sovereignty in the context of global political, economic, and technological changes of the 21st century. The study focuses on the problem of preserving and exercising sovereignty in a situation of growing interdependence of states, the weakening of supranational regulatory mechanisms (the UN, etc.), and the strengthening of the positions of major powers.
Keywords: Peace of Westphalia, sovereignty, sanction, de-sovereignization, atypical war, Bush, quasi-states, unrecognized states